Not-sew-wicked stepmom. 8 - Iru (Graphic novelist); Mo9Rang (Graphic novel illustrator) (Ize Press, 2026)
After being rescued from drowning at sea by Nadia, a strange girl with red hair who can't talk, Sabrian and Abigail invite her back to the palace as thanks. What they don't realize at first is that Nadia is actually a mermaid princess! After confirming Nadia's true identity, Abigail is faced with conflicting feelings. If she is able to put her personal feelings aside, Nerghen will gain a powerful ally in the mermaid kingdom and a happy future for Sabrian. The only problem is, Nadia's heart seems to be set not on Sabrian, but Abigail!